The Concept of Islamic Education According to Imam Ghazali in Forming the Character of Generation Z in the Digital Era - Martasila, Dimas Sari; Abidin, Zaenal (PT ARRUS Intelektual Indonesia, 2025)
This study examines how Imam al-Ghazali formulated the concept of character education for a student, with the aim of seeing the relevance of the concept of Islamic education to generation Z in the millennial era. The research method used in this study is library research, and the data analysis approach is carried out by content analysis. Documentation is used to obtain data, with the main source being the book Ihya Ulumuddin, books and scientific works related to the title that have been determined as secondary data that support the research. The findings in the study according to Al Ghazali that good character education is a way to get closer to Allah for happiness in the world and the hereafter. Generation Z as a generation that is prone to becoming bad or good quickly, there needs to be a focus on the education process and cutting off ties with the outside world when character education is carried out. The purpose of Islamic education is none other than to get closer to Allah, while the method used by Al Ghazali is actually a relevant method in the development of the era including generation Z in the digitalization era.